A “win-win situation overall”: lessons from tobacco industry influence of the negotiation of the North American Free Trade Agreement - Kelley Lee; Jappe Eckhardt (Tobacco Induced Diseases, 2018)
Background NAFTA was the most expansive agreement of its kind when it came into force in 1994. Contemporary trade negotiations grapple with how to deal with tobacco, but there is limited assessment of industry influence of past agreements and how adopted measures have impacted tobacco control.